THE COMMONNESS OF POSSIBILITY AND REALITY IN LANGUAGE - Saidov Olmas Rakhmatovich (Modern American Journals, 2025)
The article analyzes the phenomena of scientific research of the language system in Uzbek linguistics, the main stages of methodological exchange, issues of differentiation of formal linguistics and substantial linguistics. Opinions were also expressed about the methodology of Uzbek substantial linguistics, gradualistic linguistics, and the principle of transition from quantitative to qualitative changes in Uzbek linguistics.
Keywords: Speech realization of language possibilities, effectiveness of practical use of native language possibilities, substantive and pragmatic language research, pragmatics, practical approach.